Emotional Intelligence of Early Childhood Parents During the Covid-19 Pandemic in Indonesia - Nurbiana Dhieni; Ilza Mayuni; Juriana Juriana (Psychosophia: Journal of Psychology, Religion, and Humanity, 2022)
Many cases of violence in early childhood during the Covid-19 epidemic were carried out by their own parents. This is closely related to the emotional intelligence of early childhood parents, which is a reflection of their emotional literacy. This study aims to determine the emotional intelligence of early childhood parents in Indonesia at the time of Covid-19, with a sample of 641 early childhood parents living in the capital city of Jakarta. Data were collected using a questionnaire based on Daniel Goleman's five dimensions of emotional intelligence, namely: self-awareness, self-regulation, self-motivation, empathy, and work together. Analysis techniques used descriptive and inferential quantitative data analysis. The validity of the instruments ranged from 0.323 to 0.603 with reliability of r = 0.625 to 0.731. The results showed that most of the emotional intelligence of early childhood parents in Indonesia during the Covid-19 pandemic was in the sufficient category (78%). The absence of a correlation between work together with self-awareness (F = -0.026; p> 0.05), self-regulation (F = 0.005; p> 0.05), and empathy (F = 0.002; p> 0.005) indicated that parents still need to increase their self-sensitivity and empathy for their children so that they can do positive parenting during the Covid-19 pandemic.